Modelling and simulation of a two-zone smart building testbed using energyplus - Tang, Li Qiang (2016)
With surrounding temperature and sea level rising, due to global warming, people know are looking ways to reduce their impact. To reduce carbon footprint, one have to reduce their reliant on energy produced from fossil fuel. As buildings in Singapore contributes to a large portion of energy consumption. Through the use of three software – EnergyPlus, SketchUp and Open Studio, the project model two zone building located in Nanyang Technological University (NTU), Singapore. Starting with SketchUp, the project begins through the modelling two zone building through photo manipulation. Next, the use of Open Studio, a 3rd party GUI that work with EnergyPlus engine, the building properties and systems were created. Simulation works had compared the efficiency of the building due to materials and followed by further optimizing load schedule such as lighting, equipment and also to find suitable temperature for HVAC thermostat when there is low occupancy to achieve the behavior of a smart building to eventually observe on the energy saving yet maintaining comfort principle of smart building.